Fiscal policy and the banking system in Italy: have taxes, public spending and banks been procyclical in the long-run? - Giandomenico Piluso; Roberto Ricciuti (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper analyses the relations between the banking system fluctuations, on one hand, and taxation and public spending, on the other one, using a VECM methodology. We find some evidence of prociclicality of fiscal policy using variables such as government spending, taxes, and primary surplus. Effects in the opposite direction are much smaller. Results are quite stable over time. - Credit cycles ; fiscal policy ; procyclicality
Keywords: N13; N14; E32; E60; 330; Kredit; Konjunktur; Finanzpolitik; Steuer; Öffentliche Ausgaben; Italien